Manajemen strategis dalam membangun keunggulan bersaing pada perbankan syariah: pendekatan inovatif menuju pertumbuhan berkelanjutan - Al Arham, Rusydan Akmal (Maliki Interdisciplinary Journal, 2025)
This research analyzes strategies for building competitive advantage in sharia banking using a strategic management approach. Researchers identify existing competitive advantages, formulate main strategies, and implement and evaluate these strategies. The analysis results show that sharia banking is able to achieve competitive advantage through product and service innovation, improving service quality, strengthening branding and education, developing networks and partnerships, optimizing risk management, operational efficiency, focusing on potential market segments, and strengthening capital. To implement this strategy, careful planning, effective communication and regular evaluation are needed. Challenges such as resistance to change, resource limitations, and economic uncertainty can be overcome with the right approach. The conclusion of this research emphasizes that strategic management is very important in building sustainable competitive advantage for sharia banking amidst global competition, while maintaining compliance with sharia principles.